2016
DOI: 10.6118/jmm.2016.22.2.80
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Female Sex Hormones and Electrodiagnostic Parameters and Clinical Function in Post-menopausal Women with Idiopathic Carpal Tunnel Syndrome

Abstract: ObjectivesTo investigate the role of sex-hormonal changes in idiopathic carpal tunnel syndrome (CTS) among post-menopausal women through measuring estrogen receptor (ER) expression in their transverse carpal ligament (TCL) and serum estrogen level, as well as determine the correlation between these factors and electrodiagnostic parameters and Boston score.MethodsBiopsy samples of TCL were collected from 12 postmenopausal women who had undergone surgery for severe idiopathic CTS; control specimens were collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Carpal tunnel syndrome (CTS) as the most common type of entrapment neuropathy can lead to significant discomfort, activity restriction, or occupational disability . Conservative therapy is usually considered as the first step in the management of mild to moderate CTS . Surgical release of the median nerve at wrist is usually performed in the severe conditions considering the potential side effects of surgical intervention .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carpal tunnel syndrome (CTS) as the most common type of entrapment neuropathy can lead to significant discomfort, activity restriction, or occupational disability . Conservative therapy is usually considered as the first step in the management of mild to moderate CTS . Surgical release of the median nerve at wrist is usually performed in the severe conditions considering the potential side effects of surgical intervention .…”
Section: Introductionmentioning
confidence: 99%
“…Surgical release of the median nerve at wrist is usually performed in the severe conditions considering the potential side effects of surgical intervention . There are many conservative treatments commonly used in CTS including oral non‐steroidal anti‐inflammatory drugs (NSAIDs), wrist splints, physical agent modalities, and local injections …”
Section: Introductionmentioning
confidence: 99%
“…In addition, female’s daily activity at home may aggravate the disease. Moreover, female hormonal changes like that during the menstrual cycle and pregnancy had been proven to play a role ( 19 ). Many previous studies had recorded same results ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…This can be explained by the usual unilateral hand activity load by most of the people until complaint started, possibly due to the increased liability to trauma, then the patient starts to use the other hand ending with bilateral disease (Taylor et al, 2017). The authors in ( 19 ) had suggested the presence of inheritable variations in the carpal tunnel size or contents, which would usually manifest themselves bilaterally. This was consistent with the findings of other researcher ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation